The Structural Shift in the Poetry of Omar Al-Amiri: The Collection Roses on a Strange Coffin as an Exemplar - Obeidat, Rijan Abdoh (Dirasat: Human and Social Sciences, 2024)
Objectives: This research aims to shed light on the phenomenon of syntactic shift in the language of the poet Omar Al-Amiri, making it a stylistic feature of his poetic experience. The goal is to track the shifts to reveal their aesthetic and artistic connotations. The research also aims to identify a model of modernity in modern Jordanian poetry, represented by Al-Amiri's poetry collection: Roses on a Strange Coffin. Methodology: The research adopted the descriptive analytical method due to its features that aid in uncovering compositional shifts and their poetic aesthetics, steering clear of ready-made standards and prejudiced standardizations. Results: The results emerged from the study of a poetry collection never examined before, namely Roses on a Strange Coffin by the poet Omar Al-Amiri, considered one of the modernist poets in Jordan. It was found that he constructs his poem using modernist stylistic techniques. Through the utilization of various displacement techniques in shaping his poetic language, including attention to its different forms, presentation and delay, and deletion as a condensation and conciseness technique, he enriches the poetic text. His poetry collection is distinguished by structural shifts that contribute to enriching the poetic text, revealing artistic and semantic aesthetics in the texts of the poetry collection. Conclusion: The research concludes with the importance of revealing and analyzing stylistic techniques, specifically structural shifts in the studied poetry collection, to achieve its goal of uncovering the aesthetics of the poetic text.